MANAJEMEN PENGELOLAAN LIMBAH INDUSTRI TAHU (Studi pada Sentra Industri Tahu di Kelurahan Abian Tubuh Kota Mataram) - NI MADE NIA BUNGA SURYA DEWI (Universitas Mahasaraswati Mataram, 2020)
Industrial Waste Management is one of the serious problems in the era of industrialization. Therefore waste management must be handled early during the production process. This means that the waste treatment process must be carried out from upstream to downstream. This study aims to build a waste management optimization model with quantitative analysis conducted through focus group discussions and in-depth interviews that combine the results of producer and consumer interviews. The results showed that there are many aspects related to waste from the tofu industry in the Abian Body Village, so it made waste optimization very important.